NILAI-NILAI PENDIDIKAN KARAKTER DALAM TATA RIAS WAJAH PUNAKAWAN WAYANG ORANG SRIWEDARI SURAKARTA - Sabar Narimo; Amung Wiweko (Department of Accounting Education, Faculty of Teacher Training and Education Universitas, 2017)
The objectives of the research are: (1) to know make up characteristics of Punakawan Human Puppet of Sriwedari Surakarta; (2) to know symbolic meanings of Punakawan make up of Human Puppet of Sriwedari Surakarta; and (3) to know characters building values in Punakawan make up of Human Puppet of Sriwedari Surakarta. The result shows that the characteristics of Semar make up describe Semar as wise, calm, and religious personality. the characteristics of Gareng make up describes Semar as talk less and honest personality. The characteristics of Semar make up describes Petruk as dynamic and caring personality. The characteristics of Bagong make up describes Bagong as stubborn, creative, an, and optimistic. Character building values in Semar make up are religious, peaceful, honesty, and nasionalism. Character building values in Gareng make up are honesty, peaceful, and nasionalism. Character building values in Petruk make up are communicative, peaceful, and optimistic, and Character building values in Bagong make up are curiousity, dynamic and creative.